Cuidados desenvolvidos pelos pais de lactentes correlacionados com Denver II - Rocha, Mariana Almeida [UNIFESP] (2016)
Introduction: Human development can be understood as a summation of phenomena, the products of the relation between intrinsic and extrinsic factors, such as the environment in which it is inserted, the alimentation, a healthy relation with other human beings and attention to their basic needs. Children develop themselves by interacting with people, institutions, day care centers, schools, communities, families, among others. The poor environment in stimulus for the child decreases the chances of an adequate child development, and for it to be considered a place of good quality, it should promote physical security, protection against diseases, supply basic necessities and offer diferent experiences. Objective: To know the care activities in environments that are related to child development and correlate with the Denver II outcome. Methods: Qualitative research carried out with parents of children from 30 days to 11 months and 29 days how were attended at the Nursing Consultation in Child Care at the outpatient clinic of the Cruz de Malta Assistance Center. The method: Case study was used, and as a theoretical reference the Manual for Surveillance of Child Development Context of Integrated Management of Prevalent Diseases in Childhood. Results: The results demonstrate a relationship between the care from parents and child development, noting that these activities reflect positively or negatively the results of Denver II. Of the six case studies performed, five presented children with a Normal result in Denver II; It was verified that the children live in environments with positive characteristics and their parents take good care stimulating the development of the children, with emphasis on playful activities. But in one case, negative health care factors were identified, which did not compromise Denver II's performance, but it can compromise the development in the future, pointing out needs for interventions, and monitoring through further reviews. One case revealed negative traits in daily care, with Suspect outcome in Denver II. Final considerations: In the Nursing consultation in Child Care, the nurse must be able at an opportune moment to detect unfavorable factors of care with the parents and intervene to promote child development in the home environment. Facing this question, it is suggested a research that investigates how mothers understand and put into practice the nursing orientations related to the care and promotion of their children's development.